Delayed diagnosis of pneumonia in the emergency department: factors associated and prognosis - Bouam, Maria; Binquet, Christine; Moretto, Florian; Sixt, Thibault; Vourc’h, Michèle; Piroth, Lionel; Ray, Patrick; Blot, Mathieu (Frontiers in Medicine, 2023)
Introduction Whether a delayed diagnosis of community-acquired pneumonia (CAP) in the emergency department (ED) is associated with worse outcome is uncertain. We sought factors associated with a delayed diagnosis of CAP in the ED and those associated with in-hospital mortality. Methods Retrospective study including all inpatients admitted to an ED (Dijon University Hospital, France) from 1 January to 31 December 2019, and hospitalized with a diagnosis of CAP. Patients diagnosed with CAP in the ED (n = 361, early diagnosis) were compared with those diagnosed later, in the hospital ward, after the ED visit (n = 74, delayed diagnosis). Demographic, clinical, biological and radiological data were collected upon admission to the ED, as well as administered therapies and outcomes including in-hospital mortality. Results 435 inpatients were included: 361 (83%) with an early and 74 (17%) with a delayed diagnosis. The latter less frequently required oxygen (54 vs. 77%; p < 0.001) and were less likely to have a quick-SOFA score ≥ 2 (20 vs. 32%; p = 0.056). Absence of chronic neurocognitive disorders, of dyspnea, and of radiological signs of pneumonia were independently associated with a delayed diagnosis. Patients with a delayed diagnosis less frequently received antibiotics in the ED (34 vs. 75%; p < 0.001). However, a delayed diagnosis was not associated with in-hospital mortality after adjusting on initial severity. Conclusion Delayed diagnosis of pneumonia was associated with a less severe clinical presentation, lack of obvious signs of pneumonia on chest X-ray, and delayed antibiotics initiation, but was not associated with worse outcome.